INTEGRATION OF MAQĀṢID AL-SHARĪʿAH IN THE ISLAMIC LEGAL EDUCATION CURRICULUM - Muhammadong Muhammadong (Yayasan Nuraini Ibrahim Mandiri, 2025)
This study aims investigate the incorporation of Maqāṣid al-Sharī‘ah into the Islamic law education curriculum to reinforce the basis of justice and the applicability of Islamic law in contemporary society. This study employs a qualitative technique, including literature analysis and interviews with scholars and practitioners of Islamic law. The study's findings suggest that including Maqāṣid al-Sharī‘ah into the Islamic law curriculum may enhance students' comprehension of the overarching aims of Islamic law, namely the safeguarding of religion, life, intellect, lineage, and property. Maqāṣid principles in Islamic law education assist students learn theory and also make them think critically and be flexible when faced with new problems. In conclusion, including Maqāṣid al-Sharī‘ah into the curriculum of Islamic law education is essential for cultivating legal practitioners who comprehend social justice and can apply Islamic law more effectively in contemporary society.